In acute respiratory distress syndrome, is extracorporeal membrane oxygenation an adjuvant for “everyone”? - Broman, Lars Mikael (Journal of Thoracic Disease, 2018)
The first publication from the LUNG SAFE Investigators and the ESICM Trials Group was published in the spring 2016 (1). The primary outcome variable was the incidence of acute respiratory distress syndrome (ARDS) in the intensive care unit (ICU) according to the Berlin definition (2). The results showed the incidence for ARDS to be 10.4% over four weeks in the five continents cohort of more than 29,000 critically ill patients from 50 countries.